Hypothesis of a Broken Mirror versus Difficulties of Developing Mind Theory in People Suffering from Autism Spectrum - Literature Review and Current Research Status - Głowacka, Karolina (INSTED: Interdisciplinary Studies in Education & Society, 2019)
Disorders from autism spectrum are more and more often recognised as an important cause of social disability and they have been a subject of a rapid research development during the last decade. Combining some psychological discoveries with latest discoveries in neurobiology gives a perspective of a new and potentially strong model of both social functioning and disorders connected therewith, amongst others, with autism. The ability to understand aims and plans behind other people's actions have a crucial meaning for many social interactions. Taking into account deep social difficulties observed in autism one can expect the deterioration of understanding the goals of people suffering from autism disorders. Two influential theories: "the theory of a broken mirror" and the theory of mentalism may predict that result.